1986
DOI: 10.1901/jaba.1986.19-431
|View full text |Cite
|
Sign up to set email alerts
|

Team Sports for the Severely Retarded: Training a Side‐of‐the‐foot Soccer Pass Using a Maximum‐to‐minimum Prompt Reduction Strategy

Abstract: A program to teach three severely retarded adults to use a side-of-the-foot soccer pass was evaluated. A 9-step stimulus-response chain was taught using forward chaining. In contrast to usual practice, intensive physical prompts were provided initially to teach each response component, then systematically faded. Approximately 20 lessons (trials) were presented in 20-min sessions. A multiple baseline across subjects design showed that the three trainees achieved the no-prompt criterion after 24, 29, and 22 sess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…However, less dramatic but analogous situations are quite common in the literature on instructional technology. It has become standard practice to follow errors with statements ofdisapproval (Dunlap & Johnson, 1985;Rincover & Newsom, 1985;Schreibman, 1975), physical guidance (Haring, 1985;Luyben, Funk, Morgan, Clark, & Delulio, 1986;Sprague & Homer, 1984), session-lengthening procedures consisting of either time-out (Barrera & Sulzer-Azaroff, 1983;O'Brien & Azrin, 1972) or remedial learning trials (Nutter & Reid, 1978;Page, Iwata, & Neef, 1976;Richman, Reiss, Bauman, & Bailey, 1984), and so on. Thus, in addition to producing positive reinforcement in the form of experimenter praise, correct responses also may function to avoid aversive social and physical stimulation and to effectively reduce the duration of training sessions (this latter point is potentially significant, for it has been shown that complex setting events or stimulus situations, and not just discrete stimuli, can function as negative reinforcers [Krasnegor, Brady, & Findley, 1971], and that reduction of avoidance-session durations can itself serve as negative reinforcement [Mellitz, Hineline, Whitehouse, & Laurence, 1983]).…”
Section: Error Correction During Instructionmentioning
confidence: 99%
“…However, less dramatic but analogous situations are quite common in the literature on instructional technology. It has become standard practice to follow errors with statements ofdisapproval (Dunlap & Johnson, 1985;Rincover & Newsom, 1985;Schreibman, 1975), physical guidance (Haring, 1985;Luyben, Funk, Morgan, Clark, & Delulio, 1986;Sprague & Homer, 1984), session-lengthening procedures consisting of either time-out (Barrera & Sulzer-Azaroff, 1983;O'Brien & Azrin, 1972) or remedial learning trials (Nutter & Reid, 1978;Page, Iwata, & Neef, 1976;Richman, Reiss, Bauman, & Bailey, 1984), and so on. Thus, in addition to producing positive reinforcement in the form of experimenter praise, correct responses also may function to avoid aversive social and physical stimulation and to effectively reduce the duration of training sessions (this latter point is potentially significant, for it has been shown that complex setting events or stimulus situations, and not just discrete stimuli, can function as negative reinforcers [Krasnegor, Brady, & Findley, 1971], and that reduction of avoidance-session durations can itself serve as negative reinforcement [Mellitz, Hineline, Whitehouse, & Laurence, 1983]).…”
Section: Error Correction During Instructionmentioning
confidence: 99%
“…Several prior investigations have demonstrated effective methods for training leisure skills to individuals with developmental disabilities. For example, Luyben, Funk, Morgan, Clark, and Delulio (1986) trained 3 adults with mild mental retardation a side-of-the-foot soccer pass using chaining and prompting. The pass was analyzed into nine steps that were taught sequentially through forward chaining with a varying degree of prompts as training progressed.…”
mentioning
confidence: 99%
“…Depending on the number of behaviors involved, the initial acquisition of these response chains can be a time-consuming process requiring tens and even hundreds of prompted trials (e.g., Luyben, Funk, Morgan, Clark, & Delulio, 1986). Several methods for teaching chained responses have been reported in the literature and include backward chaining (teach behaviors in reverse order from the terminal response), forward chaining (teach behaviors in sequence starting with the initial response), and total task presentation (teach all behaviors each trial; Test, Spooner, Keul, & Grossi, 1990).…”
Section: Goals Of Prolonged Deliberate Practicementioning
confidence: 99%